Widening the Lens: Reflecting on the Mixing of System Dynamics With Action Research Alongside Work Within the Problem Structuring Methods Field; Comment on "Insights Gained From a Re-analysis of Five Improvement Cases in Healthcare Integrating System Dynamics Into Action Research" - Fran Ackermann (Kerman University of Medical Sciences, 2023)
This commentary reflects upon the insights for improvement cases reported by Holmström et al where they consider the integration of action research (AR) - a research methodology - and system dynamics (SD) - a modelling technique - to manage the complexity of patient care pathways. Whilst this combination can be effective, recognising that SD is a simulation model whereas AR is a research approach is important for both practical and conceptual reasons. In addition, some of the benefits noted can also be achieved through taking a wider examination of modelling techniques, particularly problem structuring methods (PSMs) as SD has been considered a PSM and PSMs are designed to effectively engage multi-disciplinary group members in the search for solutions as this will provide further avenues for both engagement and learning.